Morphological characterization of autochthonous sheep breeds at Matopos Research Station : a markov chain monte carlo algorithm approach. - Chipindu, Lovemore (Midlands State University, 2019)
Failure to characterize autochthonous sheep breeds may result to the extinction of the important natural resource which can easily adapt to the local variation in climate change. Environmental factors and some human practices especially artiﬁcial insemination is leading to the evolving of diﬀerent pedigrees. Price determination is an important aspect in designing pricing models, but what really contributes to the weight of autochthonous sheep breed remains as the major question which needs to be addressed. By merely looking at a sheep is it possible to deduce its body weight another question of interest arises again. This project addressed several issues associated with the characterization of autochthonous sheep by establishing the relationship between morphological traits and the body weight of an animal. The relationship was further addressed through the application of several methods namely the principal component analysis, generalized linear models, WinBugs model programming and the Markov Chain Monte Carlo Algorithm Approach. The major reason behind this project was to come up with conducive way which saves resource limited farmers of sheep in being charged exorbitant prices in trying to use the more advanced technology such as (DNA) in characterizing indigenous sheep.